Application of SWAN model for wave forecasting in the southern Baltic Sea supplemented with measurement and satellite data. (May 2023) - Sapiega, Patryk; Zalewska, Tamara; Struzik, Piotr
Abstract: The aim of the research was to implement the SWAN wave model powered by meteorological data from the COSMO model in the Baltic area, with particular emphasis on the southern regions where the SWAN model is operational. In the validation of the model, the predictive performance of the formulas was assessed: Westhuysen, Komen, Janssen, ST6. The verification of wave forecast quality, obtained with the spectral model, was carried out in two stages. The first step involved selecting the best formula using the adopted parameterizations based on short-term measurement data. After choosing the best physics formula (ST6), the model results were verified with multi-stream (measurement and satellite) data at two points representing the shallow and deepwater zones. In the open sea zone, the model calibrated based on ST6 physics obtained high correlation coefficients, above 0.95 (only for SARAL they were smaller), and in the coastal zone, the correlation coefficient was above 0.75. Highlights: ST6 physics performed better than Komen, Janssen and Westhuysen formulations for the South Baltic. Multi-stream data sources allowed for complementary and reliable model verification. A very good agreement of the measurement, model and satellite data was demonstrated. Satellite data is an excellent alternative to measurements for model verification. The SWAN can be used in basins with similar geomorphology and atmospheric circulation.